Electroacupuncture Attenuates Anxiety-Like Behaviors in a Rat Model of Post-traumatic Stress Disorder: The Role of the Ventromedial Prefrontal Cortex - Hou, Yuchao; Chen, Meiyu; Wang, Can; Liu, Lumin; Mao, Huijuan; Qu, Xiaoyi; Shen, Xueyong; Yu, Bo; Liu, Sheng (Frontiers in Neuroscience, 2021)
Electroacupuncture (EA) is a promising clinical approach to treating posttraumatic stress disorder (PTSD), yet the mechanisms whereby EA can alleviate anxiety and other PTSD symptoms have yet to be clarified. In the present report, rats underwent EA for 14 consecutive days following modified single prolonged stress (MSPS) exposure. These animals were then evaluated in open field and elevated plus maze tests (OFT and EPM), while Fos immunohistochemical staining was performed to assess ventromedial prefrontal cortex (vmPFC) functional activation. In addition, an extracellular recording and stimulation system was used to analyze vmPFC inputs into the ventral tegmental area (VTA) in these rats. Temporary vmPFC inactivation was further performed to assess whether this was sufficient to reverse the anxiolytic effects of EA. Overall, rats that underwent EA treatment spent more time in the central region (OFT) and the open arm (EPM) relative to MSPS model animals (P<0.05). These MSPS model animals also exhibited significantly fewer activated Fos-positive nuclei in the vmPFC following behavioral testing, while EA was associated with a significant relative increase in c-Fos expression in this region. The transient inactivation of the vmPFC was sufficient to reverse the effects of EA treatment on anxiety-like behaviors in MSPS model rats. MSPS and SEA rats exhibiting no differences in bursting activity between baseline and vmPFC stimulation, whereas bursting activity rose relative to baseline upon ventral mPFC stimulation in EA treated and control rats. Together, these findings indicate that the vmPFC and its inputs into the VTA are functionally linked to the anxiolytic activity of EA, implicating this pathway in the EA-mediated treatment of PTSD.